Meta-Analysis: Effect of Endometriosis and Intrauterine Device Contraceptive on Ectopic Pregnancy - Habibatullah, Afifa Intifadha; Budihastuti, Uki Retno; Widyaningsih, Vitri (Journal of Maternal and Child Health, 2022)
Background: Ectopic pregnancy is an early complication of pregnancy with high morbidity and mortality. Several studies have examined a history of endometriosis and Intrauterine Device Contraceptive (IUD) use as risk factors for ectopic pregnancy, but have shown mixed results. This study aims to analyze the influence of a history of endometriosis and IUD use on the incidence of ectopic pregnancy based on previous primary studies. Subjects and Method: This was a systematic review and meta-analysis conducted with the PRISMA flow diagram guidelines. The article search process was carried out on the PubMed, Google Scholar, Science Direct, SAGE, JSTOR, and Scopus databases, for articles published from 2005 to 2022. The keywords used were: “Endometriosis” AND “Intrauterine Contraceptive Device” OR “Intrauterine Device” OR “IUD” OR “IUCD” AND “Ectopic Pregnancy” OR “Extrauterine Pregnancy” OR “Tubal Pregnancy” OR “Pregnancy Outcomes” OR “Pregnancy Complications” AND “Multivariate” OR “Multivariable” OR “Adjusted Odds Ratio” OR “aOR ". Analysis was performed with RevMan 5.3 software. Population: pregnant women of reproductive age. Intervention: endometriosis, using the IUD. Comparison: no endometriosis, no IUD use. Outcome: ectopic pregnancy. Inclusion criteria were full-text observational study articles in English and Indonesian, with ectopic pregnancy as the outcome, analyzed multivariately by including adjusted Odds Ratio/aOR. The analysis was carried out using Review Manager 5.3 software. Results: A total of 11 articles from Asia, Europe, Africa, Australia, and North America were found to meet the criteria and were included in the meta-analysis. The results of the overall analysis of 4 articles consisting of 2 cohort studies and 2 case-control studies were that endometriosis increased the risk of ectopic pregnancy 1.39 times higher than without endometriosis (aOR = 1.39, 95% CI = 1.16-1.68; p < 0.001). The results of the analysis of 7 case-control study articles showed that the use of IUDs increased the risk of ectopic pregnancy 1.35 times compared to not using the IUD and was not statistically significant (aOR = 1.35, 95% CI = 0.45-4.03; p = 0.590). Conclusion: Endometriosis is a risk factor for ectopic pregnancy. IUD use increased the risk of ectopic pregnancy but was not statistically significant. Keywords: endometriosis, intrauterine device contraceptive, ectopic pregnancy, meta-analysis. Correspondence: Afifa Intifadha Habibatullah. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: alfimakrifatulazizahh@gmail.com. Mobile: +6285375335480.